Do Bowel Disorders Affect Holmium Laser Enucleation of Prostate Outcomes? A Retrospective Cohort Study - Kyle Tsai; Perry Xu; Jenny Guo; Nicholas Dean; Nabila Khondakar; Clayton Neill; Amy Krambeck (Therapeutic Advances in Urology, 2025)
Objectives: To review outcomes for patients with irritable bowel syndrome (IBS) or inflammatory bowel disease (IBD) who undergo holmium laser enucleation of prostate (HoLEP) for bothersome urinary symptoms related to benign prostatic hyperplasia (BPH). Methods: We performed a retrospective review of patients who had undergone HoLEP by a single surgeon between January 2021 and August 2023. Preoperative, intraoperative, and postoperative characteristics were compared between patients with an ICD-10 diagnosis of IBS or IBD and those without, using Chi-square and paired T -tests as appropriate. Results: Out of 918 men, 24 (2.6%) had a diagnosis of IBS, and 36 (3.9%) had a diagnosis of IBD. There were no differences in age, BMI, preoperative American Urological Association symptoms score (AUASS), preoperative Michigan Incontinence Symptom Index (MISI) score, and history of urinary retention or incontinence. The IBS + IBD cohort had smaller prostates (100.9 vs 124.2 mL, p  = 0.01) and shorter procedure times (57.0 vs 66.5 min, p  = 0.02) than controls. IBS patients were more likely to require anticholinergic therapy at a 3-month follow-up (31% vs 13%, p  = 0.03) and had more postoperative encounters within 90 days of HoLEP (3.7 vs 2.6, p  = 0.01). There were no differences regarding changes in AUASS and MISI scores, same-day trial of void and same-day discharge rates, or complication rates. Conclusion: IBS patients who underwent HoLEP had more symptomatic postoperative courses requiring higher rates of anticholinergic medication use and more provider interactions compared to men without IBS, despite similar AUASS and MISI scores. These trends were not observed in patients with IBD.